THE CONCEPT OF DEVELOPING A THERAPEUTIC DANCE MODEL AS AN EFFORT TO INCREASE THE INTEREST OF SANGGAR SURYA KIRANA STUDENTS - Nursilah; Marieta Sarajar , Michelle; Najla Ayu Rasyid, Putri; Alvianisa, Monik; Dame Mariana Sihombing, Lusia (International Journal of Performing Arts (IJPA), 2023)
Dance that is known by the general public is a dance that functions as a traditional ceremony, entertainment and performance. But on the one hand, dance is able to become a medium for expressing feelings, processing feelings and providing concentration. Using Margareth H. Doubler's method regarding the quality of movement, the dance therapy model was developed based on existing theories of dance therapy. The results also showed that there were changes felt in students who underwent dance therapy during four meetings as evidenced by the results of observations and interviews conducted together with students.